Law vs. reality: a comparative analysis of environmental performance and constitutions in South America - Ulloa, César; Palomeque-Rodríguez, Horacio; Zambonino, Heleana (Universidad Hemisferios, 2025)
The study of the environment has gained relevance in various disciplines and approaches, especially in the last 20 years due to natural phenomena of global impact such as climate variations. The objective of this article is to determine whether the laws passed in 10 South American countries with respect to the environment have improved living conditions. To this end, the constitutions of these countries were analyzed and contrasted with their environmental performance as measured by the Environmental Performance Index (EPI) for the year 2022. The research shows how governments have incorporated measures in favor of a healthy environment as a right to a dignified life and have even deepened the doctrine by considering nature as a subject of rights, however, the results are not always along these lines. Currently, several rankings can be consulted to establish the place occupied by countries in environmental matters. In this sense, the discussion proposed here opens the door to a broader research agenda that will make it possible to contrast these preliminary results in the future.